Re-constructing the conscious children's literature in the light of critical discourse analysis - Maceda, Emmanuel A. (1998)
This study explores the relationship of twenty-one specific texts of children's stories from the Adarna Children's Books and the ideologies being professed and perpetuated in the light of Critical Discourse Analysis (CDA). A comparative analysis between Ma. Bettina Soriano's findings found in her thesis "Social Values Depicted in the Aklat Adarna's International Edition Series: A Content Analysis" (1997) is utilized to establish how children's literature construct/re-construct/de-construct the subjectivity of a child. Soriano's statements are quoted verbatim and adjacent to this are variables that provide a counter-argument to Soriano's findings based on Louis Althusser's (1971) assumptions and Ian Parker's (1992) criteria in identifying discourses.